Analisis Faktor Risiko Hipertensi Berdasarkan Jenis Kelamin dan Usia Di Temanggung Jawa Tengah - Tri Suraning Wulandari; Retno Lusmiati Anisah; Luthfi Fauzy Asriyanto (STIKES Ngesti Waluyo, 2025)
Hypertension is a chronic condition that cannot be cured but can be effectively managed. It often develops without symptoms as early as adolescence and may worsen with age. In adolescents, hypertension increases mortality, morbidity, and risk of future cardiovascular diseases, while also disrupting daily activities and productivity. If left uncontrolled and no early prevention efforts, it can lead to severe complications, underscoring the importance of screening across all age groups (adolescents, adults, elderly). The purpose of this study was to identify factors influencing the risk of hypertension and to analyze the relationship between age, gender and hypertension. The research employed a descriptive-analytical design with a cross-sectional approach, involving 169 respondents (113 adolescents, 2 adults, and 54 elderly individuals) who were selected through purposive sampling. Data collection involved a high blood pressure risk screening questionnaire and blood pressure measurements taken using a sphygmomanometer. The Chi-Square test was used for analysis at a significance level of <0.05. The study results showed that 76 (45.0%) respondents were not at risk, and 93 (55.0%) respondents were at risk of hypertension. A significant correlation between age and gender with the risk of hypertension was found (p-values=0.000). As a conclusion, there was a significant correlation between age and gender with the risk of hypertension (p-value = 0.000), with 55.0% of respondents at risk of hypertension.